MOBILE APPLICATION DEVELOPMENT FOR INVENTORY MANAGEMENT USING BARCODE TECHNOLOGY - Elkana Timotius (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The development of a mobile application for inventory management using barcode technology is an innovation that aims to increase efficiency and accuracy in recording and managing stock of goods. Barcode technology allows the inventory data collection process to be faster and with fewer errors, replacing manual recording methods that are prone to human error. This mobile application is designed to provide easy access and flexibility for users, allowing them to perform barcode scanning and real-time inventory data updates anytime and anywhere. In this research, application development is explained starting from the design, implementation to testing stages. The final results show that the use of barcode technology in mobile applications significantly optimizes the inventory management process, increases time efficiency, data accuracy, and reduces operational costs. This application can also be integrated with other management systems such as ERP and CRM, providing a more comprehensive view of company operations. By implementing this technology, companies can make better and faster decisions regarding inventory management, minimize the risk of stock shortages or overstocks, and overall increase business productivity and profitability. This research concludes that developing a barcode-based mobile application is a proactive and strategic solution for managing inventory in the digital era.